2019
DOI: 10.3389/fncel.2019.00310
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive Evaluation of White Matter Damage and Neuron Death and Whole-Transcriptome Analysis of Rats With Chronic Cerebral Hypoperfusion

Abstract: Background/Aims Chronic cerebral hypoperfusion (CCH) is induced by chronic deficit of brain perfusion, contributes to a persistent or progressive cognitive dysfunction, which is characterized by diverse neuropathological manifestations. There are currently no effective medications available. White matter damage (WMD) and cortical neuron death may be caused by CCH, which are related to cognitive impairment, while the underlying molecular mechanisms remain unclear. In the study, a database of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The onset of CCH is in the associative cortical areas; then, it spreads throughout the brain via the neuronal network, affecting cognitive function [33]. Our previous studies also showed that CCH resulted in hypoperfusion of cortical cerebral blood flow in rats, as well as white matter fiber injury and neuron death in the cortex [7,9]. Considering cerebral white matter is comprised of nerve fibers that interconnect neurons in the cortex or the deep structures [34], pathological changes in the cerebral cortex caused by CCH could also be associated with cognitive impairment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The onset of CCH is in the associative cortical areas; then, it spreads throughout the brain via the neuronal network, affecting cognitive function [33]. Our previous studies also showed that CCH resulted in hypoperfusion of cortical cerebral blood flow in rats, as well as white matter fiber injury and neuron death in the cortex [7,9]. Considering cerebral white matter is comprised of nerve fibers that interconnect neurons in the cortex or the deep structures [34], pathological changes in the cerebral cortex caused by CCH could also be associated with cognitive impairment.…”
Section: Discussionmentioning
confidence: 96%
“…Unfortunately, the neurorestorative potential of the adult brain is very limited [8]. Previous studies have reported that neuronal death is the key factor for cognitive impairment in CCH [7,9,10], with CCH patients often suffering long-term neurological deficits and cognitive impairment in the process of cerebral hypoperfusion [2]. Indeed, a previous study indicated that patients with vascular cognitive impairment exhibited typical neuron loss [11].…”
Section: Introductionmentioning
confidence: 99%
“…The MWM test was conducted in a black and circular pool that was partially filled with water at a temperature of 23 ± 1°C. The test methods have been described previously (Li et al, 2019a , b ). All experimental rats performed four training sessions each day for five consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…The stages of CCH are mainly characterized by pathological changes, such as oxidative stress, glial cell activation, inflammatory factor release, energy metabolism disorders, abnormal neuronal electrical activity, white matter damage (Li et al, 2019a ), and hippocampal neuronal damage that result in cognitive impairment (Li et al, 2019a , b ). Neuronal death is a hallmark of cognitive disorders that are induced by CCH, especially at later stages (Chen et al, 2017 ; Li et al, 2019a , b ). These changes can also be accompanied by or lead to abnormal brain structure and function at later stages of CCH.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the potential mechanisms of CCH-induced VaD are related to hippocampal neuronal injury, white matter damage, neuroin ammation, and oxidative stress. Among these factors, neuroin ammation has recently received increased attention [12][13][14][15] . Neuroin ammation mainly occurs through the activation of microglia and subsequent production of neurotoxic pro-in ammatory cytokines, which further induce neuronal damage and even neuronal death, resulting in brain damage [16,17] .…”
Section: Introductionmentioning
confidence: 99%